Sediment and residual feed from aquaculture water bodies threaten aquatic environmental ecosystem: Interactions among algae, heavy metals, and nutrients. (15th January 2023) - Kong, Wenwen; Xu, Qijie; Lyu, Honghong; Kong, Jia; Wang, Xin; Shen, Boxiong; Bi, Yonghong
Abstract: The effect of sediment and residual fish feed on aquaculture water bodies has gained increasing attention to alleviate the eutrophication and heavy metals enrichment induced by aquaculture. Thus, this study intended to reveal the possible interactions among nutrients, heavy metals, and Chlorella vulgaris ( C. vulgaris ) in aquaculture water bodies containing fish feed and sediment. The analyses showed that consistent with the composition of heavy metals in fish feed, manganese (Mn) and zinc (Zn) accounted for the highest proportions (68–78%) of heavy metals in sediment. Meanwhile, sediment in the centre of aquaculture water bodies (S2) contained more heavy metals than those in the perimeter (S1), but the released concentrations and rates ( R release ) of heavy metals from S1 were higher than those from S2. Moreover, the biomass, growth rate, specific growth rate, and nitrogen and carbon fixation rate of C. vulgaris increased with adding fish feed, whereas superoxide dismutase (SOD) and malondialdehyde (MDA) decreased. In addition, with C. vulgaris, influenced by the release process from sediment and the uptake by C. vulgaris, the concentration and R release of Mn, Pb, Cu, Mn, Cr and Cd from sediments coexisting with fish feed in water first increased and then decreased in general. The C. vulgaris biomass was significantly negatively related to Mn, Pb, Cu, Ni, Cr, and Cd and PO4 3– P ( P  < 0.05), which was caused by the uptake of C. vulgaris and indicated that C. vulgaris biomass is easily affected by these factors. Accordingly, the input of residual fish feed and sediment should be controlled. Graphical abstract: Image 1 Highlights: Mn and Zn accounted for the highest proportions of heavy metals in sediment. The toxicity of heavy metals from sediment to algae attenuated by fish feed. Residual fish feed simulated the fixation of nitrogen and carbon by C. vulgaris. C. vulgaris growth was easily affected by Mn, Pb, Cu, Ni, Cr, and Cd and PO4 3– P.